Learned Brain Self-Regulation for Emotional Processing and Attentional Modulation: From Theory to Clinical Applications - Francisco Javier Zamorano (Frontiers Research Topics, 2016)
Mounting evidence in the last years has demonstrated that self-regulation of brain activity can successfully be achieved by neurofeedback (NF). These methodologies have constituted themselves as new tools for cognitive neuroscience establishing causal links between voluntary brain activations and cognition and behavior, and as potential novel approaches for clinical applications in severe neuropsychiatric disorders (e.g. schizophrenia, depression, Parkinson´s disease, etc.). Current developments of brain imaging-based neurofeedback include the study of the behavioral modifications and neural reorganization produced by learned regulation of the activity of circumscribed brain regions and neuronal network activations. In a rapidly developing field, many open questions and controversies have arisen, i.e. choosing the proper experimental design, the adequate use of control conditions and subjects, the mechanism of learning involved in brain self-regulation, and the still unexplored potential long-lasting effect on brain reorganization and clinical alleviation, among others. This special issue on self-regulation of the brain of emotion and attention using NF approaches interested authors to report technical and methodological advances, scientific investigations in understanding the relation between brain activity and behaviour using NF, and finally studies developing clinical treatment of emotional and attentional disorders. The editors of this special issue anticipate rapid developments in this emerging field.